Synthesis of D-Fructose-Based Bifunctional Primary Amine-Thiourea Organocatalysts and Their Applications in Asymmetric Reactions - Samson Lalhmangaihzuala; Vanlalngaihawma Khiangte; Zathang Laldinpuii; Lal Nunnemi; Joute Malsawmsanga; Gospel Lallawmzuali; Thanhming Liana; Chhakchhuak Lalhriatpuia; Zodinpuia Pachuau; Khiangte Vanlaldinpuia (Chemistry, 2023)
The preparation of a new class of six bifunctional thiourea organocatalysts having a D-fructose scaffold and a primary amino group was demonstrated. In the present study, the novel organocatalysts exhibited excellent enantio- and moderate diastereoselectivities in the asymmetric Michael addition of aliphatic ketones and 1,3-diketone to substituted nitroolefins at room temperature. In addition, the direct asymmetric aldol reaction between cyclic aliphatic ketone and aromatic aldehydes was also studied in the presence of the saccharide-thiourea organocatalysts giving excellent yield with moderate enantioselectivity.